(-4,6)
The x value changes bc since it is a reflection y cannot change and x becomes negative
Answer:
idfk lol hehe hope this helps
Step-by-step explanation:
A. This is the original equation: 2x + 3 - 1 = x + 5
b. 2x + 2 = x + 5 ← combined like terms on left side
2x + 2 - 2 = x + 5 - 2 ← used inverse operation to collect constants on right side
2x = x + 3 ←simplified each side
2x - x = x - x + 3 ←used inverse operation to collect variable terms on left side
x = 3 ← simplified each side
answer x = 3
c. 2(3) + 3 - 1 = 3 + 5
6 + 3 - 1 = 8
9 - 1 = 8
8 = 8
Answer: Work
Step-by-step explanation: do i get brainliest?
It could be 2,048 cause 4096 divided by 2 equals 4096